Field Evaluation Of Temephos And Agniquer Mmf Against Immature Stages Of Anopheles Arabiensis Patton (Diptera: Culicidae) The Vector Of Malaria In Khartoum, Sudan - M. Ahmed, Bashir Adam Ismail (2007)
Two field experiments on mosquitoes were conducted in stimulated ponds at Al-sielate Agricultural Scheme of Bahary locality, Khartoum, Sudan, for a period 13 weeks (1st trial) and 9 weeks (2nd trial). A total of 30 and 25 ponds were utilized in completely randomized block design for first and second trial, respectively. Mosquito larvae and pupae were sampled using the dipping method.